Education and Family Support are The Most Influential Factors on Diet Compliance of Hypertension Patients - Angraini, Dian Isti; Lipoeto, Nur Indrawaty; Zuraida, Reni; Wijaya, Sofyan Musyabiq; Komala, Ramadhana; Febriani, Wiwi; Yunianto, Andi Eka; Rahmadhani, Eka Putri (Universitas Airlangga, 2026)
The prevalence of hypertension has continued to increase in recent years, highlighting the importance of dietary compliance among patients. This study aimed to analyze the factors influencing the dietary compliance of patients with hypertension. The study procedures were carried out using an observational analytical method with a cross-sectional design from April to October 2023 in the working area of the Kedaton Public Health Center in Bandar Lampung City. The sample population comprised 100 patients diagnosed with hypertension for at least the last 3 months who agreed to participate. The study variables were age, sex, knowledge, education, family income, attitude, motivation, self-efficacy, family support, food availability, psychological factors, health worker support, and diet compliance. Data were collected through interviews and validated questionnaires. Diet compliance was measured based on 2×24-hour food recall and compared with the standards (Recommended Daily Allowance). The data obtained were analyzed using chi-square and logistic regression analyses. The results showed that only 19% of patients with hypertension were compliant with the diet. In addition, knowledge, level of education, family income, attitude, motivation, self-efficacy, family support, food availability, psychological factors, and health worker support influenced diet compliance in patients with hypertension (p<0.05). The most influential factors were education and family support. The results of this study show the importance of educational interventions and increasing the role of the family in supporting the successful diet management of hypertensive patients to maintain normal blood pressure and prevent complications.